Cultural Studies with Communities in South Africa: Implications for Participatory Development Communication and Social Change Research - Lauren Dyll; Keyan G. Tomaselli (Social Sciences)
This article theorizes the role of local and indigenous culture in its intersection with development initiatives. It argues that Communication for Development and Social Change (CDSC), through a cultural studies framework, strengthens the potentiality of democratization and participation within community-based development and social change settings. We advocate that applied cultural studies can facilitate agency (through voice and self-representation) in social interventions. This is a cultural studies approach that has been recontextualised from the Birmingham origin as read through Marxist development studies, first adapted and mobilized during the anti-apartheid struggle in developing cultural strategy, and more recently with efforts to indigenise research practices with research participants in the southern Kalahari. We draw on an example of the community-owned, state-funded, and privately operated !Xaus Lodge cultural tourism asset. We illustrate how CDSC strategies, influenced by applied cultural studies, can work with an agentic imperative to effect development and mutual understanding in a defined geographical area, where multiple stakeholder agendas, cultural backgrounds, and ontologies are to be negotiated.